1976
DOI: 10.1144/sjg12010001
|View full text |Cite
|
Sign up to set email alerts
|

The Belhelvie mafic igneous intrusion, Aberdeenshire—a re-investigation.

Abstract: Synopsis A total field ground magnetic survey and a programme of shallow drilling have been used to augment conventional mapping techniques in the preparation of a new map of the poorly exposed Belhelvie igneous intrusion. The revised map differs considerably from previous maps and increases the landward area of the intrusion by 6 km 2 . Several new rock units have been found including a thin noritic band on the western margin, a septum of country rock which split… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…7). It is also noteworthy that a recent investigation (Ashcroft and Wilson 1976) has shown that the structure of the Old Red Sandstone inlier at Turriff (Fig. 7) is largely determined by three sets of steeply dipping faults striking approximately 020°, 060° and 145°.…”
Section: Faultsmentioning
confidence: 84%
See 3 more Smart Citations
“…7). It is also noteworthy that a recent investigation (Ashcroft and Wilson 1976) has shown that the structure of the Old Red Sandstone inlier at Turriff (Fig. 7) is largely determined by three sets of steeply dipping faults striking approximately 020°, 060° and 145°.…”
Section: Faultsmentioning
confidence: 84%
“…Elsewhere, on the NE contact of the intrusion the metasedimentary specimen from drillhole 53 is too highly altered for satisfactory petrological assessment, but the occurrence of a xenolithic, 'mixed' rock in drillhole 50 may indicate that this portion of the outer boundary of the intrusion has not been disturbed by later events. Ashcroft and Boyd 1976;Ashcroft and Wilson 1976;Blyth 1969;Boyd and Munro 1978;Duncan 1974;Johnson and Stewart 1960;Munro 1970;Read 1956. The trends of the late cleavage in the Cabrach area are as shown in Fettes 1971.…”
Section: Country Rocks Adjoining the Intrusionmentioning
confidence: 96%
See 2 more Smart Citations
“…Not only is there a distinct area of olivine-flee, two-pyroxene gabbros and norites (represented by B15), but the compositions of the orthopyroxene (En78.6), clinopyroxene (Ca44.4Mg45.7Feg.9; Mg#s2.2 ) and plagioclase (Wadsworth, 1988). Reconnaissance studies of the cumulates occurring to the east of the country rock septum, described by Ashcroft and Boyd (1976), are consistent with the lithological evidence that these rocks represent a repetition of the main sequence. The troctolites sampled in drill core from Hillhead (near Balmedie Quarry) appear to be from near the base of this succession, and contain cumulus olivine (Fogy) and cumulus plagioclase (Ans4).…”
Section: Cryptic Variationmentioning
confidence: 99%